2022
DOI: 10.1155/2022/2910411
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Profiling, Bioactive Composition, and Biological Applications of Lepidium sativum L.

Abstract: The roots, leaves, and seeds of Lepidium sativum L., popularly known as Garden cress in different regions, have high economic importance; although, the crop is particularly cultivated for the seeds. In traditional medicine, this plant has been reported to possess various biological activities. This review is aimed at providing updated and critical scientific information about the traditional, nutritional, phytochemical, and biological activities of L. sativum. In addition, the geographic distribution is also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 106 publications
1
29
0
Order By: Relevance
“…Obesity is also associated with liver disease. Over time, liver damage results in scarring (cirrhosis), which can lead to liver failure, a life-threatening condition [ 145 , 146 ]. Under this topic, Xie et al [ 147 ] reported on the impact of diosgenin on transforming growth factor (TGF)- β 1-induced hepatic stellate cells and its mechanism of action for antifibrotic effects.…”
Section: Pharmacological Properties Of Diosgenin: Underlying Molecula...mentioning
confidence: 99%
“…Obesity is also associated with liver disease. Over time, liver damage results in scarring (cirrhosis), which can lead to liver failure, a life-threatening condition [ 145 , 146 ]. Under this topic, Xie et al [ 147 ] reported on the impact of diosgenin on transforming growth factor (TGF)- β 1-induced hepatic stellate cells and its mechanism of action for antifibrotic effects.…”
Section: Pharmacological Properties Of Diosgenin: Underlying Molecula...mentioning
confidence: 99%
“…The synergistic combination of arctigenin and quercetin has been studied in two prostate cancer cell lines, LAPC-4 and LNCaP. The results indicate that this combination can inhibit the expression of oncogenic miRs miR21, miR-19b and miR-148a in LAPC-4 and miR21 and miR-148a in LNCaP cell line way more effectively than quercetin alone [162][163][164].…”
Section: Synergistic Mechanisms Of Quercetin With Anticancer Drugs An...mentioning
confidence: 99%
“…Oxidative stress is triggered by an imbalance between the amount of reactive oxygen species/free radicals, which cause harmful effects, and the body’s natural antioxidant defense mechanisms [ 125 , 126 ]. In recent decades, research has focused on finding natural antioxidant substances that can neutralize the negative potential of free radicals [ 127 , 128 , 129 ].…”
Section: Other Pharmacological Propertiesmentioning
confidence: 99%